2019
DOI: 10.1016/j.jpainsymman.2018.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Safe and Appropriate Use of Methadone in Hospice and Palliative Care: Expert Consensus White Paper

Abstract: Methadone has several unique characteristics that make it an attractive option for pain relief in serious illness, but the safety of methadone has been called into question after reports of a disproportionate increase in opioid-induced deaths in recent years. The American Pain Society, College on Problems of Drug Dependence, and the Heart Rhythm Society collaborated to issue guidelines on best practices to maximize methadone safety and efficacy, but guidelines for the end-of-life scenario have not yet been dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 83 publications
0
46
0
2
Order By: Relevance
“…Although many recommendations for methadone rotation exist, the NCCN panel members find the recommendations on the starting doses of methadone outlined in the "Hospice and Palliative Medicine White Paper" to be the easiest to implement. 94 Because the starting dose may need to be titrated up, it is essential to provide the patient with access to adequate, shortacting, breakthrough pain medications during the titration period. The NCCN Guidelines recommend monitoring for drug accumulation and adverse effects, particularly over the first 4 to 7 days, and caution that a steady state may not be reached for several days to 2 weeks.…”
Section: Methadonementioning
confidence: 99%
See 1 more Smart Citation
“…Although many recommendations for methadone rotation exist, the NCCN panel members find the recommendations on the starting doses of methadone outlined in the "Hospice and Palliative Medicine White Paper" to be the easiest to implement. 94 Because the starting dose may need to be titrated up, it is essential to provide the patient with access to adequate, shortacting, breakthrough pain medications during the titration period. The NCCN Guidelines recommend monitoring for drug accumulation and adverse effects, particularly over the first 4 to 7 days, and caution that a steady state may not be reached for several days to 2 weeks.…”
Section: Methadonementioning
confidence: 99%
“…102 The NCCN panel supports the use of baseline and follow-up electrocardiogram for patients treated with methadone as outlined in published recommendations and for patients with cardiac disease, or when methadone is used in patients taking other medications also known to prolong QTc (including TCAs). 94,103 electrocardiogram monitoring should be considered within the patient's goals of care and risk/benefit ratio as discussed with the patient. The following measures may be considered to correct QTc prolongation:…”
Section: Methadonementioning
confidence: 99%
“…It has been shown that patients under the care of physicians with low knowledge of guidelines have worse pain control. 11 The 2019 consensus recommendations by McPherson et al 8 provide expert recommendations on the safe and appropriate use of methadone in hospice and palliative care. We report here findings of the first study to evaluate the impact of implementing a standardized internal protocol for methadone rotation relative to consensus recommendations for patients seen by an inpatient palliative care service in a single academic medical center.…”
Section: Discussionmentioning
confidence: 99%
“…A recent white paper (hereafter defined as consensus recommendations) described consensus recommendations from a panel of 15 experts on the appropriate use of methadone in palliative care patients. 8 The panel reviewed the limited literature and the American Pain Society's existing guidelines on methadone use to develop guidance specific to the palliative care and hospice patients. Their recommendations covered appropriate candidates, risk assessment, drug interactions, dosing, and electrocardiogram (ECG) monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the dose may be increased by up to 5 mg per day 5 to 7 days after initiation, and by 10 mg per day every 5 to 7 days thereafter. 37 However, the National Comprehensive Cancer Network's 2016 guidelines do not limit the initial dose, and clinicians experienced with its use may adopt a more aggressive titration method with close monitoring. 37,44 A prescriber who is unfamiliar with methadone should seek consultation with a pain or palliative care specialist.…”
Section: Titration Maintenance and Discontinuationmentioning
confidence: 99%